The clinical benefit of array-based comparative genomic hybridization for detection of copy number variants in Czech children with intellectual disability and developmental delay - Marketa Wayhelova; Jan Smetana; Vladimira Vallova; Eva Hladilkova; Hana Filkova; Marta Hanakova; Marcela Vilemova; Petra Nikolova; Barbora Gromesova; Renata Gaillyova; Petr Kuglik (BMC, 2019)
Abstract Background Chromosomal microarray analysis has been shown to be a valuable and cost effective assay for elucidating copy number variants (CNVs) in children with intellectual disability and developmental delay (ID/DD). Methods In our study, we performed array-based comparative genomic hybridization (array-CGH) analysis using oligonucleotide-based platforms in 542 Czech patients with ID/DD, autism spectrum disorders and multiple congenital abnormalities. Prior to the array-CGH analysis, all the patients were first examined karyotypically using G-banding. The presence of CNVs and their putative derivation was confirmed using fluorescence in situ hybridization (FISH), multiplex ligation-dependent probe amplification (MLPA) and predominantly relative quantitative polymerase chain reaction (qPCR). Results In total, 5.9% (32/542) patients were positive for karyotypic abnormalities. Pathogenic/likely pathogenic CNVs were identified in 17.7% of them (96/542), variants of uncertain significance (VOUS) were detected in 4.8% (26/542) and likely benign CNVs in 9.2% of cases (50/542). We identified 6.6% (36/542) patients with known recurrent microdeletion (24 cases) and microduplication (12 cases) syndromes, as well as 4.8% (26/542) patients with non-recurrent rare microdeletions (21 cases) and microduplications (5 cases). In the group of patients with submicroscopic pathogenic/likely pathogenic CNVs (13.3%; 68/510) we identified 91.2% (62/68) patients with one CNV, 5.9% (4/68) patients with two likely independent CNVs and 2.9% (2/68) patients with two CNVs resulting from cryptic unbalanced translocations. Of all detected CNVs, 21% (31/147) had a de novo origin, 51% (75/147) were inherited and 28% (41/147) of unknown origin. In our cohort pathogenic/likely pathogenic microdeletions were more frequent than microduplications (69%; 51/74 vs. 31%; 23/74) ranging in size from 0.395 Mb to 10.676 Mb (microdeletions) and 0.544 Mb to 8.156 Mb (microduplications), but their sizes were not significantly different (P = 0.83). The pathogenic/likely pathogenic CNVs (median 2.663 Mb) were significantly larger than benign CNVs (median 0.394 Mb) (P < 0.00001) and likewise the pathogenic/likely pathogenic CNVs (median 2.663 Mb) were significantly larger in size than VOUS (median 0.469 Mb) (P < 0.00001). Conclusions Our results confirm the benefit of array-CGH in the current clinical genetic diagnostics leading to identification of the genetic cause of ID/DD in affected children.